2003
DOI: 10.1124/dmd.31.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Hexamethyldisiloxane and Decamethylcyclopentasiloxane in Fischer 344 Rat Urine—A Comparison of a Linear and a Cyclic Siloxane

Abstract: were obtained using a high-pressure liquid chromatography (HPLC) system equipped with a radioisotope detector. The metabolite elution was carried out on a C 18 column using an acetonitrile/ water mobile phase. The structural assignments were based on GC-MS analysis of the tetrahydrofuran extract of urine containing the metabolites. Some of the metabolites in the extracts were first protected with trimethylsilyl groups prior to GC-MS analysis using bis(trimethylsiloxy)trifluoroacetamide or highly purified hexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 14 publications
3
47
0
Order By: Relevance
“…Due to the lack of reports on hepatic metabolism rates of linear methyl siloxane analogues, our speculation about their metabolism rates trend could not be proved. However, the trends were consisted with results for the cyclic methyl siloxanes in a previous report, 37 which showed that the metabolism rate of D4 was faster than that of D5.…”
Section: Methyl Siloxanes In Plasma Samples Of Current Workers and Resupporting
confidence: 50%
“…Due to the lack of reports on hepatic metabolism rates of linear methyl siloxane analogues, our speculation about their metabolism rates trend could not be proved. However, the trends were consisted with results for the cyclic methyl siloxanes in a previous report, 37 which showed that the metabolism rate of D4 was faster than that of D5.…”
Section: Methyl Siloxanes In Plasma Samples Of Current Workers and Resupporting
confidence: 50%
“…Due to their lower volatility, elimination rates of linear siloxanes via exhalation in fat would be lower than those of cyclic compounds. In addition, it was reported that hexamethyldisiloxane (L2) could be metabolized via oxidation in liver (Varaprath et al, 2003). L8-L10, as the homologues of L2, could undergo the similar metabolism.…”
Section: Accumulation and Eliminationmentioning
confidence: 99%
“…CES (2005a) summarises the available mammalian uptake and metabolism data for D4 [including a number of unpublished studies and taking into account published work by Varaprath et al (1999Varaprath et al ( , 2003, , Andersen et al (2001), and Sarangapani et al (2003) on both D4 and D5]. Most of the available mammalian toxicokinetic and toxicity data were obtained using inhalation exposure (as this is one of the primary routes of exposure of humans and, given the volatility of D4, it is significantly easier to test the substance by this route of exposure than by dermal and oral routes), but dermal and oral exposure have also been considered.…”
Section: Science Report -Environmental Risk Assessment Report: Octamementioning
confidence: 99%